Campus Artistic Atmosphere and Student Learning Performance: Evidence from Guangxi Universities - Yang Qi; Ding Shuo Ze (SCAD Independent, 2026)
This study examines the relationship between campus artistic atmosphere and student learning performance in universities in Guangxi, China. Using a quantitative cross-sectional survey design, data were collected from 420 undergraduate students through stratified random sampling across academic disciplines and year levels. The study measured campus artistic atmosphere through three dimensions: artistic environment, participation in artistic activities, and artistic perception and resonance. Learning performance was evaluated based on learning motivation, behavior, cognitive ability, and learning outcomes. Data were analyzed using descriptive statistics and stratified linear regression analysis. The findings reveal that campus artistic atmosphere significantly predicts student learning performance (β=.779, p<0.001), explaining 60.7% of the variance in learning outcomes. Although students generally reported positive perceptions of campus artistic atmosphere, actual participation in artistic activities and intrinsic learning motivation remained relatively limited. The study argues that an artistic atmosphere becomes educationally meaningful not merely through aesthetic exposure but through emotional engagement and participatory interaction. The findings highlight the importance of culturally responsive and emotionally supportive educational environments in strengthening student engagement and holistic learning development, particularly in multicultural and resource-constrained higher education contexts.